Changes in survival of >3800 patients with metastatic colorectal cancer in Germany: results from a 16-year prospective longitudinal real-world data analysis - N. Marschner; T. Seufferlein; K. Potthoff; M.-O. Zahn; J. Uhlig; S. Dörfel; A. Karcher; A. Sauer; C. Maintz; S. Fruehauf; U. Hutzschenreuter; S. Tech; et al. (ESMO Real World Data and Digital Oncology)
Background: Results from recent clinical trials, showing median survival times of >30 months for patients with metastatic colorectal cancer (mCRC), set a new benchmark for first-line treatment. As, however, most patients are treated outside of trials, evidence from population-based studies is warranted to evaluate whether survival times translate to real world. Patients and methods: Data on treatment and outcome of 3816 patients with mCRC, observed between 2006 and 2022, were collected from 166 sites in Germany into the prospective Tumor Registry Colorectal Cancer. Data were analyzed according to start of first-line palliative treatment, divided into three time periods (2006-2010, 2011-2014 and 2015-2018). Overall survival (OS) was estimated using the Kaplan–Meier method. Results: Most patients received doublet chemotherapy (CTx) across all time periods (about 82%). The use of triplet combination CTx increased over time from 0.9% (2006-2010), over 1.3% (2011-2014) to 5.6% (2015-2018). More patients received anti-epidermal growth factor receptor antibodies over time (2006-2010: 6.5%; 2011-2014: 18.7%; 2015-2018: 25.3%). Median OS for patients who started palliative treatment between 2006 and 2010, 2011 and 2014 and 2015 and 2018 was 21.4 months [95% confidence interval (CI) 20.3-23.1 months], 21.9 months (95% CI 20.8-23.4 months) and 22.9 months (95% CI 21.8-24.9 months), respectively. Conclusion: Since the successful introduction of doublet chemotherapy with monoclonal antibodies, median OS of patients with mCRC in clinical practice remained unchanged at about 22 months over a period of 16 years. As such, our data highlight the need for new treatment options to further improve survival of patients with mCRC.